2011
DOI: 10.1002/0471142301.nsa01es57
|View full text |Cite
|
Sign up to set email alerts
|

Transfection by Electroporation

Abstract: Electroporation--the use of high-voltage electric shocks to introduce DNA into cells--can be used with most cell types, yields a high frequency of both stable transformation and transient gene expression, and, because it requires fewer steps, can be easier than alternate techniques. This unit describes electroporation of mammalian cells, including ES cells for the preparation of knock-out, knock-in, and transgenic mice. Protocols are described for the use of electroporation in vivo to perform gene therapy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…The current study showed that comparing to the Bio-Rad electroporation buffer, the OptiMEM-GlutaMAX was compatible with iPS cells in terms of transfection rate and cell viability. However, unlike reported by Potter et al (15), conducting the electroporation in ice-cold medium did not improve the transfection efficiency in the current study, although the transfection efficiency of ice-cold medium was almost independent of pulsing condition.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study showed that comparing to the Bio-Rad electroporation buffer, the OptiMEM-GlutaMAX was compatible with iPS cells in terms of transfection rate and cell viability. However, unlike reported by Potter et al (15), conducting the electroporation in ice-cold medium did not improve the transfection efficiency in the current study, although the transfection efficiency of ice-cold medium was almost independent of pulsing condition.…”
Section: Discussioncontrasting
confidence: 99%
“…marina is a naked dinoflagellate that had a difficult time withstanding the physical forces used in previously reported dinoflagellate transformation methods. Electroporation is a gentler method, allowing DNA to pass through temporary pores in an organism's membrane and has been utilized in many organisms, but requires the removal of seawater and replacement with electroporation buffers, often unable to maintain the osmolality of marine organisms 61 . A new electroporation model, Lonza's 4D-Nucleofector, provides a user with a score of built-in pulse settings and solutions that remove salts but help maintain dinoflagellates osmolality.…”
Section: Effectiveness Of Dna Introduction Methodsmentioning
confidence: 99%
“…However, in contrast to viral vectors with optimized strategies for cell transduction, nonviral vectors are still characterized by relatively low transfection efficiencies. Sonoporation, 14 electroporation (nucleofection) 15 and magnetofection 16 are interesting tools under development to enhance uptake of genetic material into cells.…”
Section: Introductionmentioning
confidence: 99%